Hubungan Antara Layanan Informasi Karir Dan Efikasi Diri Dengan Pengambilan Keputusan Studi Lanjut Siswa - Ita Kurniawati, Yuraida; , Dr. Taufik, M.Si (2015)
This study aims to determine the relationship between careers information service and self efficacy with decision making of advanced study. The hypothesis proposed by researchers is that there is a relationship between careers information service and self efficacy with decision making of advanced study. This type of research is a quantitative correlation with the data collection technique using a scale. The technique used to take the cluster random sampling. The subjects of the study are the students of the XII grade of Senior High School which amounts 124 students that consist of 43 boys and 81 girls. The research location is in Sukoharjo city. The data are collected with three scales, careers information service, self efficacy, and decision making of advanced study. Based on the data analysis using multiple regression analysis, there is a significant relationship between careers information service and self efficacy with decision making of advanced study. Effective contribution of careers information service and self efficacy for decision making of advanced study is 39,7 %. The result of the relationship between careers information service and self efficacy is positive to decision making of advanced study. It means, as better the careers information service and self efficacy, decision making of advanced study will increase. The implication of this study in the field of education is decision making of advanced study can be better by increasing carrers information services and self efficacy.